2019
DOI: 10.1039/c9cp04648h
|View full text |Cite
|
Sign up to set email alerts
|

Low energy optical excitations as an indicator of structural changes initiated at the termini of amyloid proteins

Abstract: We study the optical properties of amyloid aggregates relevant for neurodegenerative disease using experiments and computation. The low energy optical absorption in the near-UV range depends on conformations and involves charge-transfer excitations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 45 publications
2
32
1
Order By: Relevance
“…We next investigated whether the above structures also display fluorescence excitation and emission properties as has been observed for amyloid-like structures reported previously (5,40,41). Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…We next investigated whether the above structures also display fluorescence excitation and emission properties as has been observed for amyloid-like structures reported previously (5,40,41). Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The more glutamine residues in the poly-glutamine polymer, the faster the aggregation propensity of the polypeptide chain. This led us to investigate whether L-glu on its own under conditions which normally promote fibril formation, such as an increase in temperature (14), was able to form structures with similar optical properties, as recently observed for amyloid fibrils (5, 29, 30).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…It was suggested that the hydrogen bonds and, in specific cases, the aromatic stacking, can underlie these optical properties. 1,20 Yet, other views have suggested impurities and oxidation as alternative mechanisms, ascribing no significant role to the molecular arrangement. 21 Indeed, oxidation of aromatic moieties is known to result in the formation of fluorescent products.…”
Section: Introductionmentioning
confidence: 99%
“…However, this cannot readily explain the emergence of intrinsic fluorescence upon aggregation of non-aromatic species. 6,19,20 Overall, the key evidence to distinguish between these options and elucidate the mechanism of intrinsic fluorescence upon aggregation was so far missing. We believe that the reversible transitions between the luminescent and non-luminescent states upon controllable change of aggregate structure is such an evidence.…”
Section: Introductionmentioning
confidence: 99%